MiR-125a-5p impairs the metastatic potential in breast cancer via IP6K1 targeting. (1st November 2021) - Minini, Mirko; Senni, Alice; He, Xingkang; Proietti, Sara; Liguoro, Domenico; Catizone, Angela; Giuliani, Alessandro; Mancini, Rita; Fuso, Andrea; Cucina, Alessandra; Cao, Yihai; Bizzarri, Mariano
Abstract: The deregulation of PI3K/Akt signaling is among the most causes in inducing the acquisition of a metastatic phenotype in breast cancer cells, leading to Epithelial-Mesenchymal Transition (EMT). Inhibition of the PI3K/Akt pathway is known to be beneficial in the clinical setting. However, the activation of secondary pathways and toxicity profiles of available inhibitors, hindering optimal therapeutic results. Preliminary studies showed that myo -Inositol inhibits the PI3K/Akt pathway by exerting a pleiotropic anti-tumor action. Herein, we demonstrate that myo -Inositol triggers a prompt and profound remodeling of delineated expression pattern in triple-negative breast cancer cells (MDA-MB-231). Consequently, it inhibits metastasis and tumor progression through miR-125a-5p transcription and the subsequent inhibition of IP6 K1. In contrast, hormone-responsive breast cancer cells (MCF-7) are insensitive to myo -Inositol. This is due to the persistence of MDM2 synthesis promoted by estrogen-dependent pathways. Conversely, the counteraction of estrogen effects recovered the sensitivity to myo -Inositol in the hormone-responsive model. Overall, these results identify a novel axis primed by miR-125a-5p to downregulate IP6 K1 gene that inhibits metastasis. Thus, administration of myo -Inositol can activate this axis as a molecular target therapy in breast cancer. Highlights: myo- Inositol decreases metastatic spreading in triple negative breast cancer. miR-125a-5p drives anti-tumor activity of myo- Inositol by inhibiting IP6 K1. The metastatic potential is hampered by miR-125a-5p overexpression in breast cancer.